The Effect of The Example Non-Example Learning Model on The Learning Outcomes Of Grade IV Students In Science Learning - Hendrik Dunan Harianja; Lisbet Novianti Sihombing; Eva Pasaribu (STABN RADEN WIJAYA WONOGIRI, 2023)
This study aims to determine: The Effect of Example Non Example Learning Model on the Learning Outcomes of Class IV Students in Science Learning at UPTD SD Negeri 091273 Pematangsiantar Academic Year 2025/2026. The type of research used in this study is quantitative research, which states that quantitative research is research in the form of numbers and its analysis uses statistics. The research design used is an experiment using the